2017
DOI: 10.3390/foods6100091
|View full text |Cite
|
Sign up to set email alerts
|

Review of Black Soldier Fly (Hermetia illucens) as Animal Feed and Human Food

Abstract: Food futurists accept that sustainability-minded humanity will increasingly incorporate insects as alternative protein. The most studied and easily reared species are not necessarily the most sustainable, acceptable, or delicious. Here, we review the literature on the black soldier fly, Hermetia illucens, which is capable of efficiently converting a wide variety of organic materials, from food waste to manure, into insect biomass. They can be grown and harvested without dedicated facilities and are not pestife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
409
0
30

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 580 publications
(447 citation statements)
references
References 150 publications
(241 reference statements)
8
409
0
30
Order By: Relevance
“…In this respect, BSF has shown great flexibility as it can be used to reduce volume and add value to various wastes . The available literature has highlighted that the BSF life cycle and nutritional composition are noticeably influenced by the rearing substrate, with the crude protein (CP) content of the larvae ranging from about 317 to 630 g kg −1 dry matter (DM) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, BSF has shown great flexibility as it can be used to reduce volume and add value to various wastes . The available literature has highlighted that the BSF life cycle and nutritional composition are noticeably influenced by the rearing substrate, with the crude protein (CP) content of the larvae ranging from about 317 to 630 g kg −1 dry matter (DM) …”
Section: Introductionmentioning
confidence: 99%
“…8,11,12 The available literature has highlighted that the BSF life cycle and nutritional composition are noticeably influenced by the rearing substrate, 13,14 with the crude protein (CP) content of the larvae ranging from about 317 to 630 g kg −1 dry matter (DM). 7,15,16 In 2014, around 90 million tons of slaughter and vegetable WS were produced in Europe (EUROSTAT (http:// appsso.eurostat.ec.europa.eu/nui/show.do?dataset=env_ wasgen&lang=en)). Considering the Italian context, 54% of the total production of waste and agro-industrial by-products is generated by the manufacture of vegetable products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, vermicomposting can apparently reduce greenhouse gases that might occur in landfills (Adhikari et al ., ; Schott et al ., ; Nigussie et al ., ), and even process organic leachates (Popa and Green, ). Among the various types of vermicomposting, utilizing the black soldier fly (BSF) larvae ( Hermetia illucens ) as a bioreactor has been commonly adopted to treat a variety of organic materials, including animal manure, FW, distillers’ grains, and municipal slurry (Popa and Green, ; Cickova et al ., ; Wang and Shelomi, ). The harvested larvae biomass is commonly regarded as a value‐added feed for livestock(Cickova et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hereof, a possible collaboration between the local body and private non-profit organizations may lead to the com-mercial success of BSFL composting, though the assessment of local condition is quite mandatory. Although the concept of "waste is a misplaced resource" has been established among the literate people, but still, a greater fraction of the society has a psychological barrier to endorse the waste-derived products as a substitution to the similar virgin goods [111]. Zhang et al [112] worked on the aspect of implementation in China and concluded that the development of market and technology transfer can make this technique dominant over the other methods.…”
Section: Resultsmentioning
confidence: 99%